Grounding Urban Governance on Housing Affordability: A Conceptual Framework for Policy Analysis. Insights from Vienna - Peverini, Marco (PARTECIPAZIONE E CONFLITTO, 2021)
Growing and attractive cities, such as Vienna, globally face housing crises. Urban land rent (inflated by the huge housing demand in attractive areas and the consequent housing shortage) is transferred to housing prices and results in increasingly unaffordable and inaccessible cities. Housing affordability is a critical factor for enjoying the use value of housing and the broader set of values associated with cities. To assure urban agglomerations’ inclusiveness and spatial justice, urban governance should be "grounded" on affordability by redistributing land rent and keeping housing prices hooked on income levels. However, the relation between urban land rent and housing affordability is rarely connected in Housing studies. Furthermore, it is often neglected by urban governors, generally competing to increase housing prices and attract investments. This article contributes to fill this policy/research gap and offers new conceptual avenues for the analysis of urban housing affordability governance. A theoretical basis and a coherent analytical framework for policy analysis are empirically applied in a case study of the city of Vienna, focusing on affordable rental housing. Based on peculiarities—of history, political stability, and a solid welfare system—the Viennese case offers relevant insights for disentangling the complex network of policies and institutions that ground urban growth on affordability.